Antecedent of Purchase Intention for Life Insurance in India - Mittal, Monika (Digital Repository of Theses, 2024)
Insurance is considered as a tool for managing risks and providing financial security. Human life is regarded as the most precious asset in the earth and life insurance is to be considered as one kind of measure to provide financial protection to a person and his family at the period of uncertain dangers or any disaster such as uncertain death or accident. Life insurance assists individuals save money while defending against any personal risks or hazards in their life. But the Penetration of the life insurance in India is only3.2 % and laspsation rate is high then various developed countries. To improve the effectiveness of distribution channels and generate more revenue, insurance companies have begun to provide online insurance services, reducing transaction costs and increasing the speed of service. But the sale of insurance via online is only 1%. Therefore, to have a better understanding of customer and provide the insurance marketer with a tool for tapping customers’ mind this investigate the factors affecting customer intention to purchase life insurance using TPB and TAM. Based on a sample of 429 individuals, this study is basically descriptive in nature and used primary on demographic data and constructs of both the theories. The analysis has been done using SPSS and AMOS. Based on the proposed theoretical model, six hypotheses are tested. The result and finding shows that all the hypothesis is accepted. Perceived ease of use and perceived usefulness positively affects the attitude. Social norm, PCB and attitude positively affects the intention to purchase the life insurance in India. The paper will be helpful for marketer to gain a better understanding of customer and the factors that make them interested or intended to purchase life insurance in India.